Experimental determination of some nuclear decay data in the decays of 177Lu, 186Re and 124I. (March 2016) - Luca, Aurelian; Sahagia, Maria; Ioan, Mihail-Razvan; Antohe, Andrei; Savu, Beatris Luminita
Abstract: A detailed experimental study of the radionuclides 177 Lu, 186 Re and 124 I was conducted at IFIN-HH, Radionuclide Metrology Laboratory. Absolute photon emission intensities in the decays of these radionuclides were measured by high-resolution gamma-ray spectrometry. Half-life measurements using a well-type ionization chamber were also performed. These new experimental results will be useful for the future updates of the existing nuclear decay data evaluations, offering reliable and accurate data for the users. Highlights: 177 Lu, 186 Re and 124 I studies are necessary for nuclear medicine applications. Accurate nuclear decay data needed for these nuclides were measured. Half-life values were determined using a 4πγ ionization chamber. Photon emission intensities were measured by gamma-ray spectrometry. These new results will be used for future nuclear decay data evaluations.